Development of Differential Pulse Anodic Stripping Voltammetry Technique for Cadmium(II) Detection and Its Application in Water Spinach - Putra, Budi Riza; Aristri, Manggar Arum; Rohaeti, Eti; Wahyuni, Wulan Tri (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Cadmium is a toxic pollutant that is harmful to the environment and humans. The purpose of this research was to develop a method for cadmium(II) detection using differential pulse anodic stripping voltammetry (DPASV) using a glassy carbon electrode. The developed method was then applied for cadmium detection in the vegetable samples which is water spinach. The developed method was optimized in several parameters such as potential window, deposition potential, deposition time, and scan rate. The developed method for cadmium(II) detection was also investigated in its analytical performance includes linearity, precision, detection limit, and quantitation limit. The optimum conditions for cadmium(II) detection in 0.1 M KCl using DPASV technique obtained such as potential window from -1200 to -100 mV, deposition potential of -1100 mV (vs Ag/AgCl), and deposition time of 360 s. It was obtained good linearity for cadmium(II) detection using the DPASV technique with an R2 of 0.996. The precision was expressed as %SBR with 0.66%. The detection and quantitation limits for cadmium(II) detection were 0.4206 ÂµM 0.0771 ppm and 0.5525 ÂµM 0.1013 ppm, respectively. The developed method was then applied for cadmium(II) measurement in the water spinach sample and the obtained cadmium(II) concentration in water spinach was 0.2399 mg/Kg.